Exploration of the Application of the Peer Tutoring Method to Improve Reading Skills of Fourth Grade Students: A Case Study at SDN Tanjung Waras: Implementation of Peer Tutoring Method to Improve Reading Skills - Enni Maria; Endang Susilowati (Primary Education Insight, 2025)
The low reading skills of some fourth-grade students at Tanjung Waras Public Elementary School require more effective and supportive learning strategies. This study aims to evaluate the implementation of the peer tutoring method in improving reading skills and examine its impact on students' motivation and social dynamics. The study used a descriptive case study approach with stages of diagnostic assessment, implementation of peer tutoring through the "Antaca" team, daily observations, informal interviews, and evaluation of reading development. Data were collected naturally and analyzed qualitatively through the stages of data presentation, reduction, interpretation, and conclusion drawing, as well as through source triangulation. The results showed that peer tutoring can be applied systematically and creates a non-intimidating learning environment, supported by picture-based teaching materials that facilitate the decoding process. The findings also revealed significant improvements in reading fluency, letter recognition accuracy, and students' courage in reading aloud. In addition, this method has a positive impact on learning motivation and social dynamics, marked by increased self-confidence, mutual support, and a more harmonious classroom atmosphere. The study concluded that peer tutoring is effective as a pedagogical strategy for improving basic literacy and building an inclusive classroom climate. The implications of the research confirm that teachers can adopt this approach to strengthen reading learning, especially in classes with heterogeneous abilities.